Potential Association Between the Low-Energy Plasma Structure and the Patchy Pulsating Aurora - Liang, Jun; Nishimura, Y.; Donovan, E.; Yang, B.; Angelopoulos, V. (Frontiers in Astronomy and Space Sciences, 2021)
While the pulsating auroral phenomena have been recognized and studied for decades, our understating of their generation mechanisms remains incomplete to date. In one main class of pulsating auroras which is termed “patchy pulsating auroras” (PPA), the auroral patches are found to basically maintain their shape and size over many pulsation cycles. Also, PPAs are repeatedly found to essentially co-move with the ExB convection drift. The above properties led many researchers to hypothesize that PPA might connect to a structure of enhanced cold plasma in the magnetosphere. In this study, we review the existing evidence, and provide new perspective and support, of the low-energy plasma structure potentially associated with PPA. Based on observations from both the magnetosphere and the topside ionosphere, we suggest that ionospheric auroral outflows might constitute one possible source mechanism of the flux tubes with enhanced low-energy plasma that connect to the PPA. We also review the existing theories of pulsating auroras, with particular focus on the role of low-energy plasma in these theories. To date, none of the existing theories are complete and mature enough to offer a quantitatively satisfactory explanation of pulsating auroras. At last, we suggest a few future research directions to advance our understanding of pulsating auroras.